From Positive to Negative Zero-Field Splitting in a Series of Strongly Magnetically Anisotropic Mononuclear Metal Complexes - Novitchi, Ghénadie; Jiang, Shangda; Shova, Sergiu; Rida, Fatima; Hlavička, Ivo; Orlita, Milan; Wernsdorfer, Wolfgang; Hamze, Rana; Martins, Cyril; Suaud, Nicolas; Guihéry, Nathalie; Barra, Anne-Laure; et al. (Inorganic chemistry, 2017)
A series of mononuclear [M(hfa) (pic) ] (Hhfa = 1,1,1,5,5,5-hexafluoro-2,4-pentanedione; pic = 4-methylpyridine; M = Fe , Co , Ni , Zn ) compounds were obtained and characterized. The structures of the complexes have been resolved by single-crystal X-ray diffraction, indicating that, apart from the zinc derivative, the complexes are in a trans configuration. Moreover, a dramatic lenghthening of the Fe-N distances was observed, whereas the nickel(II) complex is almost perfectly octahedral. The magnetic anisotropy of these complexes was thoroughly studied by direct-current (dc) magnetic measurements, high-field electron paramagnetic resonance, and infrared (IR) magnetospectroscopy: the iron(II) derivative exhibits an out-of-plane anisotropy (D = -7.28 cm ) with a high rhombicity, whereas the cobalt(II) and nickel(II) complexes show in-plane anisotropy (D ∼ 92-95 cm ; D = 4.920 cm ). Ab initio calculations were performed to rationalize the evolution of the structure and identify the excited states governing the magnetic anisotropy along the series. For the iron(II) complex, an out-of-phase alternating-current (ac) magnetic susceptibility signal was observed using a 0.1 T dc field. For the cobalt(II) derivative, the ac magnetic susceptibility shows the presence of two field-dependent relaxation phenomena: at low field (500 Oe), the relaxation process is beyond single-ion behavior, whereas at high field (2000 Oe), the relaxation of magnetization implies several mechanisms including an Orbach process with U = 25 K and quantum tunneling of magnetization. The observation by μ-SQUID magnetization measurements of hysteresis loops of up to 1 K confirmed the single-ion-magnet behavior of the cobalt(II) derivative.